Psychological preparation of the 2004 South African Olympic team - Gahwiler, C (South African Journal of Sports Medicine, 2007)
Background. The 2004 Athens Olympics represented the greatest opportunity for psychological preparation yet afforded a multicode South African team. A coordinating psychologist was appointed a year before the event, with access to financial and other resources. Aim. The purposes of this paper are fourfold: (i) to describe a 5-stage model used for the psychological preparation of the 2004 South African Olympic team; (ii) to report on the athletes and their management teams’ perceptions of its efficacy; (iii) to describe the perceived positive and negative determinants of these same subjects’ state of mind at the Olympics; and (iv) to make recommendations for the existing model’s further improvement. Results. The psychological preparation was well received, with almost all athletes and coaches requesting an expansion thereof in the future. Recommendations are made for the model’s improvement, particularly for its ongoing implementation throughout the 4-year Olympic cycle